Evaluasi Kesesuaian Lahan dan Interaksi Faktor Pembatas Tanaman Kopi Arabika (Coffea arabica L.) Berbasis Kriteria Sys Di Pagerharjo, Kulon Progo - Marcko Ferdian Nanariain; Krishna Aji; Eka Widyawati Wijaya Kusuma; Vinny Wasty Nanariain; Endah Ratnaningsih; Rahayu Widowati (Program Studi Agroteknologi INSTIPER, 2026)
Land suitability plays a critical role in determining the productivity and sustainability of Arabica coffee cultivation, particularly in areas with complex environmental conditions. This study aimed to evaluate land suitability and analyze the interaction of limiting factors for Arabica coffee cultivation in Pagerharjo, Kulon Progo. A field survey method was employed using land mapping units as the basis of analysis. Soil physical and chemical properties, topographic conditions, and climate data were collected through field observation, laboratory analysis, and secondary data sources. Land suitability was assessed using Sys criteria, which integrate climate, soil, and topographic characteristics through a semi-quantitative and interpretative approach. The results showed that land suitability was dominated by moderately suitable class (S2), with several units classified as highly suitable (S1), and a small portion as marginally suitable (S3). The main limiting factors included temperature (tc), oxygen availability (oa), rooting conditions (rc), and erosion hazard (eh), which interactively influenced land performance. Improvements such as organic matter addition, drainage enhancement, and soil conservation increased land suitability from actual to potential conditions. However, temperature remained a persistent limiting factor due to its role in regulating plant physiological processes and its dependence on macro-environmental conditions. This study demonstrates that land suitability is determined by complex interactions among soil, topography, and climate rather than single factors. The Sys-based approach provides a more comprehensive evaluation by capturing these interactions and identifying both manageable and permanent constraints. These findings highlight the importance of integrated land evaluation for site-specific management and sustainable development of Arabica coffee cultivation.